Localization Based Energy Optimisation in Hetrogenious Wireless Sensor Network - Anshuman Prakash Singh, Prof. (Dr.) S. HasanSaeed (International Journal of Advanced Science and Technology, 2020)
Before discussing localization-based energy optimization in heterogeneous wireless sensor networks, we must have drawn a lot of attention after the recent advances of wireless technology. This paper has based the combination of localization and energy optimization, which is very helpful to the monitoring of a moving object in dense areas—a sensor node design for the purpose of collecting, synthesizing, preserving and transferring to another node. So a collection of this node formed a sensor network which we use to detect the moving object .many application of sensor network like animal protecting, military areas, forest saving, climate-changing, and so on. In this paper, we apply energy optimization in a heterogeneous wireless sensor network to localize the moving object. In this algorithm, we use Trilateration Algorithm to find three nodes at a minimum distance and calculate the RSSI (Received signal strength indicator) then apply DPR (dual prediction Mechanism). And calculate the predicted location of the desired node and this node becomes Cluster Head and then Prediction accuracy and Absolute Tracking Error of X and Y Coordinates is Calculated.